Livro didático de matemática dos anos iniciais: uma análise sobre a proposta de ensino de sequências - Rocha, Yasmin Rodrigues da (2024)
This research aimed to analyze the diversity of types of sequencing activities proposed in Mathematics textbooks from 1st to 5th grade in a collection approved by the PNLD 2023. The research approach is predominantly qualitative, as the investigation is descriptive and interpretive of the data. To collect and systematize the data, we used analysis sheets and tables. In classifying the skills addressed in the activities, we drew up the following categories of analysis, based on the theoretical framework adopted: giving continuity to the sequence; identifying patterns in sequences from different contexts; translating the pattern and regularity of a sequence into other representations; completing a given sequence with one or more missing elements; finding a close term from a given sequence; finding a distant term from a given sequence; identifying the position occupied in the sequence by a given element, considering the generalization and structure of the element; drawing up a generalization in natural language of the law of formation of a sequence; producing a sequence from pre-established terms or criteria; drawing up sequences. Another category used in the work referred to the different representations of sequences. As a result of the research, the collection's proposal 9ncludee a diversity of representations of sequences and some categories of algebraic skills aimed at generalization are almost absent, as are those that propose argumentation and exposition of thoughts in activities involving sequences.